COMPARISON OF SEVERAL PROOF SYSTEMS OF INTUITIONISTIC PROPOSITIONAL LOGIC - Sayadyan, S. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
A fragment of hierarchy of the proof systems for intuitionistic propositional logic under the p-simulation relation is constructed. These systems are resolution system, natural, Hilbert-style system and sequence system. The obtained hierarchy is the same as the hierarchy for analogous systems of classical logic.